Wave, light, and dissolved oxygen exposures drive novel coastal eelgrass (Zostera pacifica) transplant performance - Sanders, Rilee D.; Obaza, Adam K.; Grime, Benjamin C.; Lindhart, Mathilde; Miller, Luke P.; Elsmore, Kristen E.; Carmack, Olivia C.; Ford, Tom K.; Leichter, James J. (Frontiers in Marine Science, 2024)
The high ecological and economic value of seagrass has been long recognized, with these foundational habitats providing myriad ecosystem services. Yet through cumulative anthropogenic impacts, seagrasses are exhibiting extensive declines globally. A litany of studies and active restoration trials have demonstrated practical methodologies to restore seagrass habitats and effectively return critical habitat functions to degraded coastal zone systems worldwide. Seagrass loss along the U.S. West Coast has precipitated decades of seagrass protection, conservation, and restoration efforts. Yet, mitigation transplanting efforts have prioritized Zostera marina (narrow-leaved eelgrass) in shallow, protected environments, while a dearth of information is available on species inhabiting offshore islands and exposed mainland coasts. In this study, we conducted a novel transplant of Zostera pacifica, a wide-leaved species found in depths of 7 – 20 m along the offshore islands and mainland coast of California. Transplants were conducted at three geographically distinct sites in Santa Monica Bay, coupled with continuous monitoring of biophysical parameters providing insight into physical drivers at transplant and donor sites. Utilizing in situ data, and environmental thresholds adapted from the literature for Z. marina, we performed exposure analyses to evaluate factors influencing Z. pacifica transplant performance. Exceedances of threshold values for environmental parameters, specifically, wave exposure and near-bed flow speeds (Hrms > 0.59 m and Urms > 0.1 m s-1), photosynthetically active radiation (< 3 and > 5 mol m-2 day-1) and dissolved oxygen (< 3 mg O2 L-1) exposure impacted transplant survivorship. These results suggest Z. pacifica persist in biophysically dynamic conditions and are sensitive to exceedances of thresholds, underlining the importance of pre-transplant site-selection processes to this species. These data represent the first holistic study of Z. pacifica transplanting on an exposed mainland coast, which provides a view into the baseline environmental envelopes within existing Z. pacifica habitat, and further, may serve as a model for investigating scalable open coast seagrass restoration for temperate regions.